Recycling of wood for particle board production: accounting of greenhouse gases and global warming contributions - Merrild, H.; Christensen, T.H.
The greenhouse gas (GHG)emissions related to the recycling of wood waste have been assessed with the purpose to provide useful data that can be used in accounting of greenhouse gas emissions. Here we present data related to the activities in a material recovery facility (MRF)where wood waste is shredded and foreign objects are removed in order to produce wood chips for use in the production of particleboard. The data are presented in accordance with the UOD (upstream, operational, downstream)framework presented in Gentil et al. (Waste Management Research, 27, 2009). The GHG accounting shows that the emissions related to upstream activities (5 to 41 kg CO2-equivalents tonne-1 wood waste)and to activities at the MRF (approximately 5 kg CO2-equivalents tonne-1 wood waste)are negligible compared to the downstream processing (-560 to -120 kg CO2- equivalents tonne-1 wood waste). The magnitude of the savings in GHG emissions downstream are mainly related to savings in energy consumption for drying of fresh wood for particleboard production. However, the GHG account highly depends on the choices made in the modelling of the downstream system. The inclusion of saved electricity from avoided chipping of virgin wood does not change the results radically (-665 to -125 kg CO2-equivalents tonne-1 wood waste). However, if in addition it is assumed that the GHG emissions from combustion of wood has no global warming potential (GWP)and that the energy produced from excess wood due to recycling substitutes energy from fossil fuels, here assumed to be coal, potentially large downstream GHG emissions savings can be achieved by recycling of waste wood (-1.9 to -1.3 tonnes CO2-equivalents tonne-1 wood waste). As the data ranges are broad, it is necessary to carefully evaluate the feasibility of the data in the specific system which the GHG accounting is to be applied to.
Keywords: WOOD WASTE; WASTE MANAGEMENT; WOOD RECYCLING; PARTICLE BOARD; GLOBAL WARMING POTENTIAL; CO2; GREENHOUSE GAS ACCOUNTING; GREENHOUSE GASES